O Projeto Político-Pedagógico - PPP nas escolas públicas da zona sul do município de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The aim of this research is the Political Pedagogical Project – PPP in the public schools of the Southern Zone of Manaus. The study presents public policies on democratic management of public education, conceptions and configurations of PPP, it analyzes policies and actions of municipal power and the construction and implementation of the political - pedagogical project of two public elementary schools in the city school system in according to government policies established for the national and local education process and the focus democratic management. The research prioritizes the categories of analysis of the dialectical method and uses qualitative approach to document analysis and interviews. The documentary sources include plans, programs, reports, regulations, laws of teaching, pedagogical guidance, script preparation of PPP. The interviews cover the following subjects: managers (principals), teachers, professors, parents and / or guardians, administrative support services and / or teaching, representatives of the school council and the local community. The survey shows that the plans and programs implemented by SEMED, to some extent, insert guidelines for democratic management in basic education in particular the preparation of PPP. The interviews show that the actions of SEMED regarding the construction of the political - pedagogical project are reflected in fast formations and limited advice to managers and educators. The segments of the school and local community recognize the importance of PPP and collective actions as a guiding instrument in school processes, and agree with the need to reformulate this mechanism, however, still bring a conception of the completed document. Participation in the preparation of the PPP school and local community School the process was more expressive than School B, bringing together much of the segments. The two schools had difficulties greater participation from parents and / or guardians by conflicting work hours of meetings with school and teachers by working conditions in most days with other schools. The survey results suggest a reflection of the guidelines formulated by the municipal power to Manaus from the political - pedagogical project towards strengthening this instrument in processes of democratic governance with the participation of the school and local community and thus contribute to improving the quality of public education.
Keywords: Políticas Públicas; Gestão Democrática; Projeto Político-Pedagógico; Public Policy; Democratic Management; Political-Pedagogical Project; CIÊNCIAS HUMANAS: EDUCAÇÃO